A simple method to simultaneously achieve synchronization and anti-synchronization in chaotic systems - 李瑞红 陈为胜 李爽 (Chinese physics B, 2010)
In this paper, a novel adaptive control approach is presented to simultaneously achieve synchronization and antisynchronization in partially linear chaotic systems. Through appropriately separating state vectors of such systems, synchronization and anti-synchronization could be simultaneously realized in different subspaces, which may be strictly proven theoretically. Simulation results for a Lorenz chaotic system and a new hyper-chaotic system are provided to illustrate the effectiveness of the proposed method. Finally, a new secure communication scheme based on such a synchronization phenomenon of the hyper-chaotic system is demonstrated. Numerical results show success in transmitting a periodic signal with high security.